Form, Function, and Meaning in the Use of Euphemism in the Title of Kompas Daily Newspaper - I Made Darma Sucipta; I Nyoman Mandia; I Made Rai Jaya Widanta; Jebamani Anthoney; I Nyoman Sukra; Putu Dyah Hudiananingsih (Journal of Applied Studies in Language, 2026)
This study aims to analyze the forms, functions, and meanings of euphemisms used in the news headlines of Kompas online news headlines published between September and October 2024. This topic is important because euphemism is a linguistic strategy employed by the media to convey sensitive information in a more polite, subtle, and socially acceptable manner. The study applied a qualitative approach with a descriptive-semantic method. The data consisted of 15 news headlines containing euphemistic expressions, collected through document analysis, supported by note-taking techniques. The data were analyzed by classifying them based on linguistic forms, communicative functions, and semantic meanings. The findings reveal that the dominant forms of euphemism are loanwords and borrowed terms, followed by metaphors and periphrasis. Functionally, euphemisms are used to soften expressions, maintain politeness, conceal sensitive meanings, and support diplomatic strategies in news reporting. In terms of meaning, two types of meaning were identified: conceptual meaning and associative meaning. Conceptual meaning tends to occur in loanwords, while associative meaning is more frequently found in metaphorical expressions. These findings indicate that euphemism in Kompas headlines functions not only as a linguistic feature but also as a discursive strategy to frame social reality and influence readers’ perceptions. Therefore, lexical choices in mass media play a significant role in shaping public opinion in a subtle yet effective way.